Strengthening Indonesian Constitutional and Citizenship Knowledge:: (A Critical Comparative Framework with the United States Presidential System) - Damanik, Prince Clinton Immanuel Christian; Anastasia Arta Uli; Mohammad Idham Chaled; Rizki Achmad Husaeni; Feri Dwi Jayanti (Siyasah Dusturiyah: State Law Review, 2025)
A country's constitution serves as fundamental law regulating relationships between government and citizens in various aspects including state form, institutions, human rights, citizenship rights, and national ideals. This study compares the Indonesian constitution with that of the United States through a citizenship education lens, examining how constitutional frameworks shape citizenship knowledge and civic participation. The research focuses on state structure and government systems, state institutions, human rights arrangements, citizenship provisions, and constitutional amendment mechanisms. Using a normative juridical approach with statutory and comparative methods, data is collected through literature study and presented qualitatively with descriptive-analytical approach. Results indicate that Indonesia and the United States share similarities in government form, several state institutions, human rights regulations, and constitutional amendment mechanisms, while differences emerge in state form, certain institutions, citizenship conceptualization, gun ownership rights, and judiciary involvement in constitutional amendments. The findings contribute to strengthening constitutional literacy and citizenship education, particularly relevant for Pancasila and Civic Education pedagogy in Indonesia.